1995
DOI: 10.7124/bc.0003d4
|View full text |Cite
|
Sign up to set email alerts
|

Lysogeny by MS2 phage. Analysis of a recombinant plasmid containing MS2 RNA-like sequence

Abstract: pL34 recombinant plasmid coding MS2-like RNA synthesis in plasmid-containing cells has been studied using physical mapping and blot-hybridisation with P 32-labelled pMS27 plasmid Iragmenis including a DNA copy of MS2 phage RNA. The authors have deter mined the size of a fragment containing MS2-like sequence and its localisation inside the hybrid plasmid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…PLASMID [26] In the preceding section it was shown that phagespecific RNA can be synthesized on a fragment of the chromosome of an MS2-induced E. coli mutant cloned within a recombinant plasmid. In the present section results are given from a study of a cloned fragment of the DNA of a mutant cell.…”
Section: Determining the Size Of A Fragment Of The Dna Of Recombinantmentioning
confidence: 99%
“…PLASMID [26] In the preceding section it was shown that phagespecific RNA can be synthesized on a fragment of the chromosome of an MS2-induced E. coli mutant cloned within a recombinant plasmid. In the present section results are given from a study of a cloned fragment of the DNA of a mutant cell.…”
Section: Determining the Size Of A Fragment Of The Dna Of Recombinantmentioning
confidence: 99%
“…Незважаючи на відсутність подібних даних, нами було показано в роботах [2,3], що РНК бактеріофага MS2 у процесі реплікації в інфіко ваній клітині все-таки здатна вступати в контакт з хромосомою хазяїна на рівні фізичного об'єднання фагового геному з клітинною ДНК. Це призводить до виникнення серії М82-індукованих мутантів Es cherichia colL Наступні дослідження [4,5] показа ли, що в клітинах цих М82-інду кованих мутантів продукуються з низькою частотою ДНК-вмісні бак теріофаги, які, за даними серологічних досліджень, могли б нести у своїх віріонах М82-специфічну генетичну інформацію.…”
unclassified